Synthesis and characterization of all-inorganic (CsPbBr3) perovskite single crystals. Issue 21 (22nd August 2022) - Gupta, Ramashanker; Datt, Ram; Barthwal, Swapnil; Sharma, Harshit; Pandey, Animesh; Deka, Ridip; Sarkar, Pranjit; Husale, Sudhir; Srivastava, Ritu; Gupta, Vinay; Arya, Sandeep; Pathak, Sandeep
Abstract : This work investigates the synthesis of Cesium (Cs) based all-inorganic (CsPbBr3 ) perovskite single crystals (PSCs) at low temperatures (45 °C) for application in photosensitive devices. Abstract : This work investigates the synthesis of Cesium (Cs) based all-inorganic (CsPbBr3 ) perovskite single crystals (PSCs) at low temperatures (45 °C) for application in photosensitive devices. The Cs-based PSCs are more environmentally stable in comparison with PSCs based on formamidinium and methylammonium. The crystals are grown using an inverse temperature crystallization method. The structural characterization was conducted using an X-ray diffractometer and confirms that the crystal is highly crystalline and it also shows that it belongs to the {110} family of planes. The optical analysis of the Cs-based single crystal was conducted using photoluminescence spectroscopy. The crystal has a bandgap of 2.18 eV as calculated by using the Tauc formula. Furthermore, a remarkable photocurrent analysis of the responsivity and detectivity parameters was conducted using a visible light laser (532 nm) and revealed values of ∼1 A W −1 and 3.7 × 10 11 Jones, respectively. Thus, the all-inorganic PSC, CsPbBr3, will be of benefit to optoelectronic device applications.